Review of microgrid protection strategies: current status and future prospects - Zaid Alhadrawi; Mohd Noor Abdullah; Hazlie Mokhlis (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
A microgrid is a developed form of a distribution system, which is integrated with a set of different types of distributed generation (DG) to supply local demand. In spite of that microgrids have many advantages as they increase reliability, raise efficiency, decrease feeder losses and voltage sag correction. However, there are many technical challenges faced, one of them is the protection of microgrid. Conventional protections have been made for radial distribution systems configuration. Where supplying source has one direction and the power flow is defined. The DG penetration converts the distribution network to a multi sources system causes a bidirectional power flow. Also, the most of DG uses a DC to AC converter which limit the fault current level. Therefore, a suitable protection scheme for microgrid ought to be designed to protect a microgrid from any disturbances may occur for both modes of operation grid-connected and islanded. The purpose of this paper is to summarize the challenges and problems facing microgrid protection. As well as the most strategies to date are presented with a discussion of their basic principles of operation to solve these problems. Finally, some conclusions and suggestions for microgrid protection in the future are presented.